Desain Implementasi Service Oriented Architecture (SOA) pada pembuatan Prototype Sistem Informasi Coaching Pondok Pesantren Alam Sayang Ibu (PAMSI) - Noor Alamsyah; Royana Afwani; Sri Endang Anjarwani; Moh. Ali Albar; Ahmad Zafrullah Mardiansyah (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
The presence of service-oriented computing, through the Service Oriented Architecture (SOA), and the implementation of information technology through website applications provide opportunities for more appropriate system utilization for an organization by providing options for implementing functionalities in a modular manner, according to the needs of the organization following the evolution of service growth, without the need for large Information Technology infrastructure investments. In order to develop an Coaching Information System for Pondok Pesantren Alam Sayang Ibu (PAMSI) with a service functionality basis, it is necessary to define a prototype model of Coaching Information System with an SOA approach through understanding the process of coaching activities and must be relevant to the needs of each party involved. This study aims to create a SOA implementation design that can be used as a guideline to be used as the main foundation in the creation of a PAMSI Coaching Information System and can be used as a reference for the development of other Information Systems at PAMSI.